Strengthening Family Financial Management and Investment for Parents of Students at AUM School Majelis Dikdasmen PNF PCM Gresik - Alkusani; Sukaris, Sukaris; Heru Baskoro; Indro Kirono; suwarno (OJS Universitas Muhammadiyah Gresik, 2025)
The low level of financial literacy and inclusion of Indonesian society, especially among parents with lower-middle educational and economic backgrounds, is a challenge in managing family finances. This condition influence parents' ability to meet children's educational needs and build long-term family welfare. This community service activity aims to strengthen the capacity of family financial management and investment through education and training for parents/guardians of students at AUM Sekolah Majelis Dikdasmen PNF Gresik. The method used is Community-Based Participatory Research (CBPR) which emphasizes active community participation from the planning, implementation to evaluation stages. The activity was carried out through an interactive seminar discussing three main topics: financial planning, budget management, and family investment. The results of the activity showed that out of 81 targeted participants, 20 parents attended and showed active participation. The training material was considered very relevant and applicable. The participants expressed an increase in understanding and high interest in more systematic family financial management, including the desire to continue advanced training related to investment and the use of digital budgeting tools. This activity shows that community-based educational interventions are able to increase parents' awareness and capacity in managing family finances wisely, so that they are worthy of being replicated in other communities with local adjustments.